ANALYSIS AND DESIGN OF INFORMATION SYSTEM DUE ON PT. LINTAS KARYA HARAPAN - Risman Risman; Drs. Sunarto Usna Drs. Sunarto Usna (Jurnal Sistem Informasi, 1997)
With existence of computerized information system accounts, the time and energyneeded to produce the report will be more efficient. Details of charges can beprocessed more quickly and with accurate results, it can support the decision makingprocess required by the head of the company through the information generated.